Policy Communication in Developing Frankincense Commodity in Humbang Hasudutan Regency - Purba, Arief Marizki; Indainanto, Yofiendi Indah; Safira, Citra (Talenta Publisher, 2023)
Frankincense commodities play an important role in agricultural commodity production in Humbang Hasudutan. Traditional processing has become a local wisdom that has been practiced for years. However, the threat of eroding customary forests and the lack of marketing are obstacles faced by farmers. The purpose of this research is to find out the communication of government policies in developing frankincense commodities. The method used in this research is descriptive with a qualitative approach. The results show that policy communication is able to encourage the effectiveness of frankincense agricultural development in Humbang. Policies regarding socialization to farmers to understand how the food estate program takes place, encourage community involvement in supporting the development plan. Efforts to create farmer welfare, encourage the strengthening of farmer organizations to be an important need in supporting the development of frankincense commodities. Strengthening the organization is considered capable of overcoming the problem of marketing difficulties of frankincense production from farmers.